Azure Kubernetes Service (AKS) essentials cloud Kubernetes for developers and IT professionals - Buchanan, Steve (O'Reilly Media, Inc., 2024)
Azure Kubernetes Service (AKS) Essentials is a comprehensive video course designed to take IT professionals and developers from beginner level to proficiency in utilizing Azure Kubernetes Service (AKS). AKS is a fully managed container orchestration platform provided by Microsoft Azure, offering the power of Kubernetes for deploying and managing containerized applications with ease. This course is structured to provide a step-by-step learning journey, starting from the fundamentals of AKS and gradually progressing towards advanced topics. With a hands-on approach, participants will gain practical experience by working with real-world examples, exercises, and demonstrations. By the end of this course, participants will have developed a strong foundation in Azure Kubernetes Service and will be capable of efficiently deploying, managing, and scaling containerized applications using AKS in a production environment.
Online resource; title from title details screen (O'Reilly, viewed September 16, 2024)
Keywords: Windows Azure; Application software -- Development; Cloud computing; Web applications; Logiciels d'application; Développement; Applications Web; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet